Progressive Macromolecular Self-Assembly: From Biomimetic Chemistry to Bio-Inspired Materials - Zhao, Yu; Sakai, Fuji; Su, Lu; Liu, Yijiang; Wei, Kongchang; Chen, Guosong; Jiang, Ming (Advanced materials (Weinheim), 2013)
Macromolecular self‐assembly (MSA) has been an active and fruitful research field since the 1980s, especially in this new century, which is promoted by the remarkable developments in controlled radical polymerization in polymer chemistry, etc. and driven by the demands in bio‐related investigations and applications. In this review, we try to summarize the trends and recent progress in MSA in relation to biomimetic chemistry and bio‐inspired materials. Our paper covers representative achievements in the fabrication of artificial building blocks for life, cell‐inspired biomimetic materials, and macromolecular assemblies mimicking the functions of natural materials and their applications. It is true that the current status of the deliberately designed and obtained nano‐objects based on MSA including a variety of micelles, multicompartment vesicles, and some hybrid and complex nano‐objects is at their very first stage to mimic nature, but significant and encouraging progress has been made in achieving a certain similarity in morphologies or properties to that of natural ones. Such achievements also demonstrate that MSA has played an important and irreplaceable role in the grand and long‐standing research of biomimetic and bio‐inspired materials, the future success of which depends on mutual and persistent efforts in polymer science, material science, supramolecular chemistry, and biology. Expansion into life science and material science is one of the major trends and the most important long‐time goals of modern polymer science. Our paper tries to trace the most recent footsteps of macromolecular self‐assembly in this direction. It covers the representative achievements in the fabrication of artificial building blocks for life, cell‐inspired biomimetic materials, assemblies mimicking the functions of natural materials and their applications.